BENGKEL MESIN KAPAL PERIKANAN DI DUMAI - Muchtar Ahmad (UIR Press, 2013)
Based on a survey on three boat engine workshops in Dumai, the state of small scale workshop was reported. The perspective technology, human capital, problem, and development are analyzed in order to address the problem and to promote the workshop. Actually the manager of fishing boat engine workshop is quite simple in term of technological and managerial knowledge; as they have been adopted from long experience working in the engine workshop somewhere or in the family own. The number of fishing boat engine workshop in Dumai City is not match enough to serve more than 300 hundreds small fishing boats with engine. The workshop serves to install of engine on the boat, to fix out of order engine and to serve regularly engine services. The technicians were none from engineering or mechanical vocational school, even though some of them were graduant of senior high school. As the workshop business is profitable, labor intensive and badly demanded, but the competency in workshop technology and management are limited and need of further improvement. Especially in the field of mechanical and fishing boat engine skill proficiency as well as basic and practical mechanical engineering knowledge improvement. Therefore a crash program in the vocational school and curriculum review of professional program in mechanical engineering are necessary to fulfill the badly need fishing boat engineers or technicians as well as engine workshop managers in the coastal region.